Reaktualisasi Hak Atas Pelayanan Kesehatan Mental Pasca Pandemi Covid-19 di Indonesia: Sebuah Ius Constituendum? - Zaki Priambudi; Namira Hilda Papuani; Ramdhan Prawira Mulya Iskandar (Badan Strategi Kebijakan Hukum, 2022)
The Covid-19 pandemic has increased the need for mental health services in Indonesia. However, the government hasn't prioritized the mental health aspect in handling the pandemic. The WHO has stated that the COVID-19 pandemic has created a worldwide mental health crisis. This article aims to examine whether the fulfillment of mental health is the state's responsibility, what is the urgency of the fulfillment of mental health services and how is the ius constituendum for the fulfillment of the right to mental health services in Indonesia. By combining doctrinal research and Research-Oriented Reform, this article finds that based on the UDHR, ICESCR, 1945 Constitution of the Republic of Indonesia, Health Law, and Mental Health Law stipulate that the fulfillment of mental health services is the state's responsibility. However, Indonesia law hasn't fulfilled facilities and access to mental health laws. Therefore, the article recommends three things. First, Promulgate the Psychology Practice Bill which regulates the development and management of human resources in the psychology profession. Second, Ratify the Government Regulation of the Mental Health Law regarding the procedures for implementing mental health services. Third, Ratify Regional Regulations to regulate mental health administration's planning, financing, and supervision.